FRAUDSTER'S PERSONALITY MOTIVATION SPHERE - R. Akhmetgareyev (Russian Journal of Economics and Law)
The article reveals the peculiar motivations of an individual's unlawful behaviour, when committing a fraud for property acquisition of for obtaining rights for someone else's property.